(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Oligodendrocyte development and myelination occurs vigorously during the early post natal period which coincides with the period of peak mobilization of iron. Oligodendrocyte progenitor cells (OPCs) are easily disturbed by any agent that affects iron homeostasis and its assimilation into these cells. Environmental exposure to vanadium, a transition metal can disrupt this iron homeostasis. We investigated the interaction of iron deficiency and vanadium exposure on the myelination infrastructure and its related neurobehavioural phenotypes, and neurocellular profiles in developing rat brains. Control group (C) dams were fed normal diet while Group 2 (V) dams were fed normal diet and pups were injected with 3mg/kg body weight of sodium metavanadate daily from postnatal day (PND) 1-21. Group 3 (I+V) dams were fed iron deficient diet after delivery and pups injected with 3mg/kg body weight sodium metavanadate from PND1-21. Body and brain weights deteriorated in I+V relative to C and V while neurobehavioral deficit occurred more in V. Whereas immunohistochemical staining shows more astrogliosis and microgliosis indicative of neuroinflammation in I+V, more intense OPCs depletion and hypomyelination were seen in the V, and this was partially protected in I+V. In in vitro studies, vanadium induced glial cells toxicity was partially protected only at the LD 50 dose with the iron chelator, desferroxamine. The data indicate that vanadium promotes myelin damage and iron deficiency in combination with vanadium partially protects this neurotoxicological effects of vanadium.